2001
DOI: 10.1074/jbc.m004627200
|View full text |Cite
|
Sign up to set email alerts
|

Rap1 Is Activated by Erythropoietin or Interleukin-3 and Is Involved in Regulation of β1 Integrin-mediated Hematopoietic Cell Adhesion

Abstract: The CrkL adaptor protein is involved in signaling from the receptor for erythropoietin (Epo) as well as interleukin (IL)-3 and activates ␤ 1 integrin-mediated hematopoietic cell adhesion through its interaction with C3G, a guanine nucleotide exchange factor for Rap1. We demonstrate here that Epo as well as IL-3 activates Rap1 in an IL-3-dependent hematopoietic cell line, 32D, expressing the Epo receptor. The cytokine-induced activation of Rap1 was augmented in cells that inducibly overexpress CrkL or C3G. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 45 publications
4
75
0
3
Order By: Relevance
“…Similarly, recent studies have shown that Rap1 may also interact with the Ras effector PI3K and show a negative or positive effect on activation of the PI3K/Akt pathway depending on cell types and stimuli (Tsygankova et al, 2001;Wang et al, 2001;Lou et al, 2002;Christian et al, 2003). In our previous study, we found that IL-3 as well as Epo activates b1 integrin through Rap1 and induces hematopoietic cell adhesion, which agrees with recent studies showing that Rap1 plays important roles in regulation of cell adhesion through various integrins (Arai et al, 2001;Bos et al, 2001;Stork and Dillon, 2005). However, the roles Rap1 plays in activation of downstream signaling pathways, including those involving B-Raf, Raf-1, MEK, Erk, and Akt1, in cells stimulated by IL-3 or BCR/ABL have largely remained to be examined.…”
Section: Introductionsupporting
confidence: 91%
See 4 more Smart Citations
“…Similarly, recent studies have shown that Rap1 may also interact with the Ras effector PI3K and show a negative or positive effect on activation of the PI3K/Akt pathway depending on cell types and stimuli (Tsygankova et al, 2001;Wang et al, 2001;Lou et al, 2002;Christian et al, 2003). In our previous study, we found that IL-3 as well as Epo activates b1 integrin through Rap1 and induces hematopoietic cell adhesion, which agrees with recent studies showing that Rap1 plays important roles in regulation of cell adhesion through various integrins (Arai et al, 2001;Bos et al, 2001;Stork and Dillon, 2005). However, the roles Rap1 plays in activation of downstream signaling pathways, including those involving B-Raf, Raf-1, MEK, Erk, and Akt1, in cells stimulated by IL-3 or BCR/ABL have largely remained to be examined.…”
Section: Introductionsupporting
confidence: 91%
“…The ability of TPO to activate Rap1 to mediate sustained Erk signaling agrees with the observation that several hours of stimulation with TPO are required for activation of Rap1 and is similar to that seen in the neuronal differentiation of PC12 cells stimulated by NGF (Garcia et al, 2001;Stork, 2003;Stork and Dillon, 2005). On the other hand, IL-3 stimulation rapidly induces activation of Rap1 (Arai et al, 2001), and Rap1 inactivation by SPA-1 inhibited the transient early Erk activation (Figure 2b). The difference in time course of activation of Rap1-mediated signaling between IL-3 and TPO may respond to the difference in signaling for proliferation and differentiation, although the molecular mechanisms responsible remain to be examined.…”
Section: Rap1 Activation By Bcr/abl and Il-3supporting
confidence: 86%
See 3 more Smart Citations